Ulysse et les Roumains - Catherine Durandin (Cahiers Balkaniques)
I propose to go back in time and explore the theme of the tragic journey whereby Greece and Romania finally meet across time, weaving a string of memories that stretches from antiquity to the present day. The journey is that of Jewish Romanian writer Benjamin Fondane who left his anti-Semitic Romania to write a long poem about exile in French entitled Ulysse. The tragic journey is that of Laetitia and Julien, who, after meeting by chance in December 1989 in Bucharest, were reunited by chance twenty years later in the same city, only to be separated by death when Julien was killed in a bomb attack in Constantza. Yet tragedy also generates powerful waves of tenderness and affection – the tenderness Julien’s mother feels for her son, torn as she is between lamenting and rebelling against death in an echo of all the tragic figures of the Mother from Andromaque to the universal Nanny. Here, Greek tragedy informs present-day Romania from Bucharest to Constantza as well as the terrible lament of those who mourn when death triumphs over love.